10+{7-[12-(18-2×6÷3)÷7+3÷(28÷7×9-6×4÷8×9)]÷2}×2
plssssssssss repede
Răspunsuri la întrebare
Răspuns de
0
Răspuns:
=10+{7-[12-(18-12÷3)÷7+3÷(4×9-24÷8×9)]÷2}×2
=10+{7-[12-(18-4)÷7+3÷(36-3×9)]÷2}×2
=10+{7-[12-14÷7+3÷(36-27)]÷2}×3
=10+[7-(12-14÷7+3÷9)÷2]×3
=10+[7-(12-2)÷2]×3
=10+(7-10÷2)×3
=10+(7-5)×3
=10+2×3
=10+6
=16
Alte întrebări interesante
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă